Doctor Who. The complete sixth series [videorecording (DVD)] - Darvill, Arthur, 1982-; Gillen, Karen; Smith, Matt, 1982- (Warner Home Video, 2011)
This release combines the two halves of series six with the 2010 Christmas Special plus hours of bonus material to make a spectacular collectible that no fan will want to miss! The new series includes the first ever episodes shot in the US and promises new thrills, new monsters, and new adventures which will leave fans pinned to the edge of their seats. Special features included.